2020
DOI: 10.26504/bp202104
|View full text |Cite
|
Sign up to set email alerts
|

Child poverty in Ireland and the pandemic recession

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21st Century Ireland. The Institute was founded in 1960 by a group of senior civil servants led by Dr T.K. Whitaker, who identified the need for independent and in-depth research analysis to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…While the data used in this study were gathered before the pandemic, the results underline the likely consequences of the current pandemic for children through parental unemployment, increased poverty and financial stress (see also Darmody et al, 2020, for a broader review). ESRI research has demonstrated the importance of the emergency pandemic supports, including the Pandemic Unemployment Payment and the Employment Wage Subsidy Scheme, in preserving household income and preventing an increase in child poverty (Beirne et al, 2020;Reagan and Maître, 2020). The evolution and removal of these supports will need to be cognisant of the need to protect children and young people from the longer-term damaging impacts of even transient spells of EV.…”
Section: Implications For Policymentioning
confidence: 99%
See 1 more Smart Citation
“…While the data used in this study were gathered before the pandemic, the results underline the likely consequences of the current pandemic for children through parental unemployment, increased poverty and financial stress (see also Darmody et al, 2020, for a broader review). ESRI research has demonstrated the importance of the emergency pandemic supports, including the Pandemic Unemployment Payment and the Employment Wage Subsidy Scheme, in preserving household income and preventing an increase in child poverty (Beirne et al, 2020;Reagan and Maître, 2020). The evolution and removal of these supports will need to be cognisant of the need to protect children and young people from the longer-term damaging impacts of even transient spells of EV.…”
Section: Implications For Policymentioning
confidence: 99%
“…The key role of both maternal and paternal employment in lifting families out of EV and preventing entries into poverty highlights the central importance of employment supports such as active labour market policies and the current emergency pandemic supports to prevent mass unemployment, including the Pandemic Unemployment Payment and the Employment Wage Subsidy Scheme. These supports are crucial to preventing child poverty and the devastating effects this can have in the short and longer term (see Beirne et al, 2020, andMaître, 2020, for analyses of these supports in the early part of the pandemic). Access to employment that is sufficient to lift families out of poverty also requires a policy focus on low pay, access to education and skills development, and significant public investment in affordable, high-quality childcare.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…We show that doing so using a third of the €159 million Revenue estimate that a €7.50 per tonne carbon tax increase raises would reduce the overall poverty rate by 0.2 percentage points (ppts) and leave the lowest-income fifth of households on average better-off. Using the revenue to increase IQCs would reduce the child poverty rate by twice that (0.4ppts): a substantial reduction, given Regan and Maître (2020) estimate child poverty could rise by 1.4ppts this year because of pandemic related job losses, even with some recovery.…”
Section: Executive Summarymentioning
confidence: 99%
“…These are sizeable effects. By means of reference, Regan and Maître (2020) estimate that the at-riskof-poverty rate for children could rise by 1.4 percentage points this year because of pandemic related job losses even with some recovery. The other reforms we consider -increasing the Fuel Allowance (B), increasing the personal income tax credit (D) and raising the Living Alone Increase (E) -have no effect on poverty.…”
mentioning
confidence: 99%
“…Kneewshaw et al (2021), Almeida et al (2020) and Palomino et al (2020) estimate the impact of COVID-19 on poverty for all European Union countries. In addition, country-specific studies have been conducted for Ireland (Doorley et al 2020;Regan and Maître 2020), Italy (Figari and Fiorio 2020), Finland (Kyyrä et al 2021), Germany (Bruckmeier et al 2020), and Malta (Vella and Misfud 2020). In all these studies, income-based poverty estimates are used.…”
Section: Introductionmentioning
confidence: 99%